The A.B.C. murders - Christie, Agatha, 1890-1976. (New York : Berkley, 1991)
Hercule Poirot is sent a series of letters by a murderer challenging him to try to stop a crime if he is clever enough.
"A Hercule Poirot novel.".
Young Adult
Keywords: Poirot, Hercule (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Mystery fiction; Poirot, Hercule (Fictional character) -- Fiction; Private investigators -- Fiction; England -- Fiction